Quality Assurance in Nigeria’s Education System: Prospect and Challenges - Usman, Yunusa Dangara; Chinyere, Madudili Geraldine (EduLine: Journal of Education and Learning Innovation, 2021)
The study was conducted with the aim of establishing the relevance and challenges affecting quality assurance in Nigerian education system. Secondary data analysis methodology was adopted for the study. To easily achieve the objectives, the concept of quality assurance, strategies for building quality assurance into the education system and parameters for measuring quality assurance and challenges were discussed. The study identified some challenges affecting quality assurance to include shortage of funds, insecurity, policy inconsistency, and lack of regular training of staff etc. The paper concludes that since the essence of education is to make an individual useful quality assurance strategies should be monitored and evaluated on regular basis in order to improve the quality of the educational system in Nigeria. The study therefore recommends amongst others improved funding of the education sector, regular training and retraining of staff and provision of adequate security for learning environment in the country as a way forward.